Efektivitas Metode Pembelajaran STAD (Student Teams Achievement Division) Pada Pembuatan Pola Dasar - Nabila, Fida; Yuniati, Mita (PT. Riset Press International, 2025)
The implementation of effective classroom instruction requires the use of appropriate teaching methods, as each method is designed to address specific learning problems. Selecting an instructional method that aligns with the challenges faced during the learning process is a crucial factor in optimizing student learning outcomes. This study aims to: 1.) Describe the outcomes of basic pattern-making among Grade X DPB students using the demonstration method; 2) Describe the outcomes of basic pattern-making among Grade X DPB students using the STAD (Student Teams Achievement Division) method; and 3) Analyze the effectiveness of the STAD method in facilitating the learning of basic pattern-making in Grade X DPB. This research employed a quantitative approach with a quasi-experimental design. The sample consisted of all Grade X DPB students at SMKN 1 Jatirejo. Data were collected through psychomotor performance tests, and data analysis was conducted using descriptive statistics and an independent samples t-test. The findings were derived from hypothesis testing, which revealed a p-value of less than 0.05, indicating a statistically significant difference between the two instructional methods. The average score obtained by students in the demonstration group was 66.69, while the average score in the STAD group was 81.64. Based on these results, it can be concluded that the STAD method is more effective than the demonstration method in addressing the challenges encountered in the teaching and learning of basic pattern-making.